Arterial stiffness index as a marker for the occurrence of atherosclerotic cardiovascular disease - Salih, Saba F.; Mohammed, Najeeb H.; Muslim, Abbas N.; Al-Misebawi, Sarab H. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Arterial functional changes reflected by vascular stiffness might occur at early stages of cardiovascular disease before the morphological alterations reflected by increasing the intima media thickness and it is widely used as a very sensitive indicator of functional vascular damage. Objectives: This study is aimed to correlate ultrasound detected vascular functional changes with the severity and extent of coronary artery disease. Patients and methods: Sonographic scans were performed on 100 Patients (61males, 39 females) with an age range of (40-65years) for measuring carotid and brachial arteries end diastolic and end systolic diameters to calculate vascular stiffness index . Coronary CT angiography has been used to visualize the atherosclerotic plaque to define the degree of luminal stenosis by creation of high-quality images which are obtained by the multislice CT spiral scanners. Results: A positive statistical correlation was observed between the stiffness index of both carotid and brachial arteries in single coronary lesion (SCL), multiple coronary lesion (MCL) and control groups in addition to the significant positive correlation between both arteries stiffness index with the percentage of coronary artery stenosis in SCL group. Significant difference between the arterial stiffness index among the study groups is only noticed for carotid artery between the control and MCL groups (p<0.05). Conclusion: Conduit arterial stiffness index is a good indicator of the severity and extent of coronary artery disease.